Origins of the alveolar stop -d as coda in mongolic (Altaica, 2024)
It is a well-known feature of Mongolic languages, that the voiceless, aspirated alveolar stop -th was not allowed as coda in the earlier times, even Middle Mongolian reflects a stage, where a vowel was pronounced after this consonant, which can be inferred from sources that demonstrably reflect the pronunciation of that time: